Episiotomy and obstetric perineal wound dehiscence: Beyond soreness. (April 2014) - Kamel, A.; Khaled, M.
Abstract Postpartum episiotomy dehiscence is a rare complication of vaginal delivery. Infection rates in episiotomy wounds are surprisingly low; however, it remains the most common cause of wound dehiscence, which may lead to major physical, psychological and social problems if left untreated. Most dehisced perineal wounds are left to heal naturally by secondary intention. This approach often results in a protracted period of significant morbidity for women. There is emerging evidence that early re-suturing closure of broken-down perineal wounds may have a better outcome, but randomised controlled trials are needed to yield evidence-based guidance for this management approach.